Effect on catalysis by replacement of catalytic residue from hen egg white lysozyme to Venerupis philippinarum lysozyme*. (28th June 2016) - Abe, Yoshito; Kubota, Mitsuru; Takazaki, Shinya; Ito, Yuji; Yamamoto, Hiromi; Kang, Dongchon; Ueda, Tadashi; Imoto, Taiji
Abstract: Asn46Asp/Asp52Ser or Asn46Glu/Asp52Ser hen egg white lysozyme (HEL) mutant was designed by introducing the substituted catalytic residue Asp46 or Glu46, respectively, based on Venerupis philippinarum ( Vp ) lysozyme structure as a representative of invertebrate‐type (i‐type) lyzozyme. These mutations restored the bell‐shaped pH‐dependency of the enzyme activity from the sigmoidal pH‐dependency observed for the Asp52Ser mutant. Furthermore both lysozyme mutants possessed retaining mechanisms like Vp lysozyme and HEL. The Asn46Glu/Asp52Ser mutant, which has a shorter distance between two catalytic residues, formed a glycosyl adduct in the reaction with the N ‐acetylglucosamine oligomer. Furthermore, we found the accelerated turnover through its glycosyl adduct formation and decomposition. The turnover rate estimated from the glycosyl formation and decomposition rates was only 20% of the observed hydrolysis rate of the substrate. Based on these results, we discussed the catalytic mechanism of lysozymes. Abstract : PDB Code(s):3WW5 ;3WW6